Synthesis of Some Heterotic Cycle Azolidines - Gojayeva, S.S.; Nazarov, N.M.; Babayev, S.S.; İsrafilova, Z.T. and Seyidova, S.T. and Grigoryeva, N.M. and Akhmedova, J.J. (Herald of Azerbaijan Engineering Academy, 2023)
In this article 2-thio-4-oxothiazolidine, 2-thio-4-oxo-5-methylthiazolidine, thiozolidinone2,4, 2-thiogidantone, which are highly reactive as a result of three-component condensated in the presence of various catalysts, provide ample opportunities for the synthesis of other nitrogenous heterocyclic compounds. Different thiozalidindions (tions) are synthesized. To assess the antioxidant properties of the synthesized compounds, the kinetics of their reactions with cumylperoxide radicals and cumylhydroperoxide are studied. The reaction of the studied compounds with cumyl peroxide radicals is studied on the basis of the oxidation of cumene by the reaction of the initiator AIBN at a concentration of 2 · 10-2 mol / l.